2018
DOI: 10.1108/ilt-03-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Thermal insulation effect on EHL of coated cam/tappet contact during start up

Abstract: Purpose This paper aims to investigate the lubrication performance of cam/tappet contact during start up. Especially, the thermal insulation effects of coating on the lubrication performance during cold start up process and warm start up process are studied. Design/methodology/approach A numerical model for the analysis of thermal elastohydrodynamic lubrication of coated cam/tappet contact is presented. In this model, the Reynolds equation and the energy equations are discretized by the finite difference met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Furthermore, using transient full-film TEHL simulations, Meng et al [46] concluded that amorphous carbon coating induced thermal insulation effects that are particularly beneficial in start-up processes of the cam/tappet-contact, leading to significantly reduced frictional losses. Gangopadhyay and Watt [47] used a motored valve train test-rig to determine a friction reduction of up to 35% from shallow V-shaped grooves fabricated by a diamond cutting tool.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using transient full-film TEHL simulations, Meng et al [46] concluded that amorphous carbon coating induced thermal insulation effects that are particularly beneficial in start-up processes of the cam/tappet-contact, leading to significantly reduced frictional losses. Gangopadhyay and Watt [47] used a motored valve train test-rig to determine a friction reduction of up to 35% from shallow V-shaped grooves fabricated by a diamond cutting tool.…”
Section: Introductionmentioning
confidence: 99%
“…5 Guo et al identified the temperature-viscosity-wedge effect and explained the abnormal surface-dimple phenomena observed by Kaneta et al 6,7 Meng et al presented a numerical model for the analysis of thermal elastohydrodynamic lubrication of coated cam/tappet contact. 8 Liu et al proposed a numerical method to calculate the surface thermal stresses of solids in thermal elastohydrodynamic lubrication of line contact. 9…”
Section: Introductionmentioning
confidence: 99%
“…5 Guo et al identified the temperature-viscosity-wedge effect and explained the abnormal surface-dimple phenomena observed by Kaneta et al 6,7 Meng et al presented a numerical model for the analysis of thermal elastohydrodynamic lubrication of coated cam/tappet contact. 8 Liu et al proposed a numerical method to calculate the surface thermal stresses of solids in thermal elastohydrodynamic lubrication of line contact. 9 Although these studies have examined the effect of temperature on lubrication performance, they have failed to consider how temperature affects the deformation and subsurface stress of the contact bodies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, YU [30] investigated the influence of different coatings on tribological contact behavior. MENG [31] analyzed the significance of the thermal insulation effect during start-up from the hot and cold states for the initial cam cycles. The author described that the friction losses during a cold start-up are significantly higher than the losses during a warm startup, and that a coating generally reduces the friction losses due to thermal insulation.…”
Section: Introductionmentioning
confidence: 99%